Steroids Spinal Injections - Marcia, Stefano; Zini, Chiara; Hirsch, Joshua A.; Chandra, Ronil V.; Bellini, Matteo (Seminars in Interventional Radiology, 2018)
Spinal pain is a common condition leading to significant disability and high cost. Spinal injections have been demonstrated to be effective short-term treatments with cost–utility superior to numerous other treatments, including surgical procedures. Appropriate patient selection—based on clinical and imaging finding—and the use of image guidance associated with technical precautions improve the safety and effectiveness of spinal injection and overall patient outcomes.
Keywords: spinal injection; epidural infiltration; foraminal infiltration; back pain; interventional radiology